2006
DOI: 10.1175/jpo2934.1
|View full text |Cite
|
Sign up to set email alerts
|

Interdecadal Variability of the Southern Ocean

Abstract: The intrinsic variability of the Antarctic Circumpolar Current is investigated using an idealized wind-driven model. The model uses three quasigeostrophic layers, with steady wind stress forcing, and no diabatic effects. Despite the idealized nature of the model, the simulations display a robust mode of low-frequency variability in the flow. It is demonstrated that this variability is dependent upon the explicit simulation of the dynamics of mesoscale eddies. As such, the variability is sensitive to stratifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
118
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(130 citation statements)
references
References 42 publications
12
118
0
Order By: Relevance
“…Meredith and Hogg [16] and Hogg and Blundell [26] used an eddy-resolving ocean model to simulate the response of the ACC to the zonal wind stress and found that there was a lag between the wind stress forcing and the ACC kinetic energy of approximately 2 years, which was consistent with the results of this study. The delayed response is related to the internal variability of the ACC.…”
Section: Discussionsupporting
confidence: 85%
“…Meredith and Hogg [16] and Hogg and Blundell [26] used an eddy-resolving ocean model to simulate the response of the ACC to the zonal wind stress and found that there was a lag between the wind stress forcing and the ACC kinetic energy of approximately 2 years, which was consistent with the results of this study. The delayed response is related to the internal variability of the ACC.…”
Section: Discussionsupporting
confidence: 85%
“…However, process-oriented numerical studies have shown that mesoscale eddies may drive chaotic low-frequency fluctuations in the ocean (e.g. Jiang et al, 1995;Spall, 1996;Berloff and McWilliams, 1999;Hogg and Blundell, 2006). One may then hypothesize that both the strong enhancement and (realistic) confinement in eddy-active areas of SLA variabilities at all timescales, and the aforementioned temporal decorrelation, denote the emergence at 1 4…”
Section: Discussionmentioning
confidence: 99%
“…In the following, we list specific differences which may plausibly account for variations in model sensitivity and evaluate their impact: • resolution on a Mercator grid, while MJM13 extends up to 1 6 • resolution. It is well established that improved resolution of eddies moderates the sensitivity of modelled circulation to wind stress [20]; hence, we first consider whether resolution dependence may explain some inter-model differences. However, SH12 gives a higher circumpolar transport and overturning sensitivity than even the 1 2…”
Section: Hypothesesmentioning
confidence: 99%